Facile synthesis of α-Fe2O3 micro-ellipsoids by surfactant-free hydrothermal method for sub-ppm level H2S detection. (15th November 2016) - Li, Zhijie; Lin, Zhijie; Wang, Ningning; Huang, Yanwu; Wang, Junqiang; Liu, Wei; Fu, Yongqing; Wang, Zhiguo
Abstract: The α-Fe2 O3 micro-ellipsoids were prepared using a facile hydrothermal process without any surfactant or template, and their morphological, structural and H2 S sensing properties were investigated. The α-Fe2 O3 showed uniform micro-ellipsoids with a long axis diameter of 1.7 μm and a short axis diameter of 1.2 μm. Detailed structural analysis confirmed that the synthesized α-Fe2 O3 micro-ellipsoids were compact particles with a hexagonal structure. Gas sensor base on the α-Fe2 O3 micro-ellipsoids showed excellent response, short response/recovery time (< 90 s and 30 s, respectively), low detection concentration (~ 0.5 ppm), good long-term stability and excellent selectivity towards H2 S gas at the optimized operating temperature of 350 °C. The sensing mechanism of the sensor based on the α-Fe2 O3 micro-ellipsoids towards H2 S was discussed. Graphical abstract: The micro-ellipsoids of α-Fe2 O3 were prepared using a facile hydrothermal process without any surfactant or template. The α-Fe2 O3 micro-ellipsoids based gas sensor shows a good performance to H2 S. Highlights: The micro-ellipsoids of α-Fe2 O3 were prepared using a facile hydrothermal process without any surfactant. The α-Fe2 O3 micro-ellipsoids based gas sensor shows a good performance to H2 S. The sensor possesses good reproducibility and selectivity in H2 S detection.